PENGARUH PERSEPSI MANFAAT DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUASAN KONSUMEN OVO - Abdul Yusuf; Nurul Aulia Dewi; Nada Shofiatul Ula; Alya Luthfi (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to find out the Effect of Perception of Benefits And Ease of Use on OVO Customer Satisfaction. The type of research used is associative research with quantitative approaches. by using data collection methods namely Field Research (questionnaire) and Library Research (journal & book). The number of samples used in this study was 204 respondents. The data analysis method used is simple linear regression analysis and t test. The results showed that variables perceived benefit (X1) and ease of use (X2) had a positive and significant effect on customer satisfaction (Y) because the value of tcount> ttable and the significant value was smaller than 0.05 so that Ho was rejected and Ha was accepted. This means that the perception of benefits (X1) and ease of use (X2) has an effect on customer satisfaction (Y).